Peran Asesmen Psikologi dalam Bimbingan dan Konseling - Syakira Zahira Shofa (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Psychological assessment is an important component of guidance and counseling services as it supports counselors' understanding of learners' psychological conditions, potentials, and problems. This article aims to explain the role of assessment in understanding clients, identify the types of assessments commonly used, and emphasize the importance of understanding assessment as a counselor's professional competence. This study uses a qualitative approach based on literature studies from relevant journals. The results of the discussion show that assessments, both test and non-test, can provide comprehensive information that assists counselors in designing effective interventions. Understanding assessment also encourages counselors to act professionally and ethically in the service process. Thus, assessment is not just a measuring tool, but an important foundation in holistic and strategic counseling practice.